Composite fiber, wear-resistant fabric and cushion
By using twisted composite fibers in the car seat cushion, combining PBO, polyethylene and aramid fibers, and using CNT modification treatment, the problems of insufficient wear resistance and flame retardant performance of the seat cushion are solved, and high-performance seat cushion materials are achieved.
Patent Information
- Application Number
- CN202510117285.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-08
AI Technical Summary
The existing car seat cushions are not wear-resistant, and they are prone to wear, whitening, decolorization and other phenomena after long-term use, and the flame retardant performance is poor, making it difficult to meet the high-quality needs of new energy vehicles.
Composite fibers with twisted yarn structures are specifically twisted on the aramid fiber filaments in the same direction by 1 strand of PBO fiber and 3 strands of polyethylene fiber filaments, and the wear resistance and flame retardant properties of the fibers are improved by CNT modification treatment.
It achieves excellent wear resistance and flame retardant properties of composite fibers, extends the service life of the seat cushion, and maintains good performance in high friction environments.
Smart Images

Figure CN119777043A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-performance composite fibers, and in particular to a composite fiber, a wear-resistant fabric, and a cushion. Background Art
[0002] As people's living standards improve, seat cushions are widely used in automobiles, homes, offices, public transportation and other fields. Their functions are not limited to providing comfort, but also include aesthetics, protection, etc. As a vehicle-mounted product, car seat cushions need to be able to improve the user's comfort and durability.
[0003] However, existing seat cushions generally have the problem of insufficient wear resistance. Most seat cushions are prone to wear, whitening, discoloration and other phenomena during long-term use, especially in areas with frequent friction. This greatly limits their service life and practicality. At the same time, with the vigorous development of new energy vehicles, the probability of spontaneous combustion of cars has also increased rapidly; better flame retardant performance is a high-quality requirement for the development of car seat cushions. Therefore, higher requirements are placed on the wear resistance and flame retardant properties of seat cushions. Summary of the invention
[0004] In order to overcome the above technical defects, the present invention provides a composite fiber, a wear-resistant fabric and a cushion.
[0005] In order to solve the above problems, the present invention is implemented according to the following technical solutions:
[0006] In a first aspect, the present invention provides a composite fiber, wherein the composite fiber adopts a twisted yarn structure, and the composite fiber is a strand of PBO fiber and three strands of polyethylene fiber filaments twisted in the same direction on an aramid fiber filament.
[0007] Preferably, the product specification of the polyethylene fiber filament is 22.22tex / 198f.
[0008] Preferably, the product specification of the aramid fiber filament is 131.11tex / 667f.
[0009] Preferably, the aramid fiber filaments are CNT-modified aramid fiber filaments.
[0010] Preferably, the aramid fiber filament is prepared by the following modification method:
[0011] (1) Cleaning:
[0012] The aramid fiber filaments were immersed in an acetone solution and subjected to ultrasonic treatment for 30 minutes; then rinsed with deionized water for 3-5 times, placed in a vacuum oven, vacuum dried at 60°C for 4 hours, taken out, and sealed for storage;
[0013] (2) Preparation of modified solution:
[0014] A Tris buffer reagent is prepared by using a dilute hydrochloric acid solution and tris(hydroxymethyl)aminomethane particles, and the Tris buffer is slowly added to a dopamine-HCL solution with a concentration of 2 g / L for multiple times, and the pH is adjusted to 8.5 to obtain a dopamine solution; then, 0.13% by mass of hydroxy carbon nanotube powder CNT is dissolved in anhydrous ethanol solution, and the mass ratio of the hydroxy carbon nanotube powder CNT to ethanol is 5:95, and after ultrasonic dispersion for 1-2 hours, the mixture is added to the dopamine solution, and the mixture is fully stirred and mixed to obtain a modified solution;
[0015] (3) Modification treatment:
[0016] The washed aramid fiber filaments are completely immersed in the modification solution, immersed at room temperature for 24 hours, and then rinsed with deionized water for 3-5 times; finally, dried in a vacuum oven at 60°C for 2 hours to obtain CNT-modified aramid fiber filaments.
[0017] In a second aspect, the present invention further provides a wear-resistant fabric, which is woven from the composite fiber described in the first aspect.
[0018] Preferably, the wear-resistant fabric adopts a warp knitted structure.
[0019] Preferably, the wear-resistant fabric is treated with a wear-resistant coating.
[0020] In a third aspect, the present invention further provides a seat cushion, comprising a fabric and a filler disposed inside the fabric; the fabric is made of the wear-resistant fabric described in the second aspect.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The invention provides a composite fiber. The composite fiber adopts a twisted yarn structure. The composite fiber is composed of one strand of PBO fiber and three strands of polyethylene fiber filaments twisted in the same direction on aramid fiber filaments.
[0023] In the present invention, PBO fiber has excellent flame retardancy and high strength, and ultra-high molecular weight polyethylene fiber (UHMWPE) has extremely high wear resistance and low friction coefficient, and its wear resistance is better than many traditional fibers. The wear resistance of the composite fiber is further enhanced by combining it with PBO fiber through twisting process. Aramid fiber filament itself has high strength and high modulus, which can provide stable structural support for the composite fiber and enhance the overall wear resistance.
[0024] The composite fiber of the present invention combines the high strength and flame retardancy of PBO fiber, the wear resistance of polyethylene fiber and the stability of aramid fiber, and is expected to achieve excellent wear resistance and flame retardancy in car seat cushions. At the same time, the softness and comfort of the composite fiber will not be affected by high performance requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The specific embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings, wherein:
[0026] Figure 1 The warp knitted structure of the wear-resistant fabric of the present invention;
[0027] Figure 2 is a schematic diagram of the layer structure of the seat cushion of the present invention;
[0028] 10- wear-resistant fabric, 20- silicone layer, 30- first memory foam layer, 40- second memory foam layer. DETAILED DESCRIPTION
[0029] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0030] like Figure 1 As shown, the preferred structure of the composite fiber, wear-resistant fabric and cushion described in the present invention.
[0031] The invention provides a composite fiber. The composite fiber adopts a twisted yarn structure. The composite fiber is composed of one strand of PBO fiber and three strands of polyethylene fiber filaments twisted in the same direction on aramid fiber filaments.
[0032] In the present invention, PBO fiber has excellent wear resistance, flame retardancy and high strength, and ultra-high molecular weight polyethylene fiber (UHMWPE) has extremely high wear resistance and low friction coefficient, and its wear resistance is better than many traditional fibers. The wear resistance of the composite fiber is further enhanced by combining it with PBO fiber through twisting process. Aramid fiber filament itself has high strength and high modulus, which can provide stable structural support for the composite fiber and enhance the overall wear resistance.
[0033] For common natural fibers or single fibers, their wear resistance is not good, so some synthetic fibers with better performance can be introduced, and the two can complement each other to improve the various properties of the fabric. To this end, the composite fiber of the present invention combines the high strength and flame retardancy of PBO fiber, the wear resistance of polyethylene fiber and the stability of aramid fiber, and is expected to achieve excellent wear resistance and flame retardancy in car seat cushions. At the same time, the softness and comfort of the composite fiber will not be affected by high performance requirements. Polyethylene fiber and aramid fiber have excellent wear resistance and impact resistance, can effectively resist external friction and impact, and extend the service life of the composite fiber.
[0034] In this field, twisting is a common yarn processing method. By twisting multiple fiber filaments in the same direction, the fibers can be tightly bound together. This structure can significantly improve the strength, wear resistance and fatigue resistance of the fiber. At the same time, twisting can also give the fiber a certain elasticity, so that it can better disperse stress when subjected to force and reduce local damage. This structure makes the arrangement between fibers more compact, enhancing the integrity and consistency of the fibers. The synergistic effect of multiple fibers can improve the comprehensive performance of the composite fiber.
[0035] In the art, PBO fiber (poly-p-phenylenebenzobisoxazole fiber) is a high-performance organic fiber with excellent mechanical properties, heat resistance and flame retardancy.
[0036] In a preferred embodiment, the product specification of the polyethylene fiber filament is 22.22tex / 198f. The polyethylene fiber filament of the present invention belongs to ultra-high molecular weight polyethylene fiber (UHMWPE), which has extremely high strength and modulus. It has excellent impact resistance, cut resistance, high wear resistance, chemical corrosion resistance, good flexibility and low density. The flexibility of polyethylene fiber makes the composite fiber have good flexibility and fatigue resistance, can maintain integrity during repeated bending and stretching, and is suitable for application scenarios of textile products that require frequent deformation.
[0037] In the present invention, the product specification of the aramid fiber filament is 131.11tex / 667f. 131.11tex means that the weight of each 1000 meters of fiber is 131.11 grams. 667f means that the fiber is composed of 667 single filaments. This structure with a high number of single filaments can improve the overall strength and wear resistance of the fiber.
[0038] In a preferred implementation, the aramid fiber filaments are CNT-modified aramid fiber filaments.
[0039] CNT has extremely high strength and modulus. By combining with aramid fiber, the mechanical properties of the fiber can be significantly improved. For example, studies have shown that after CNT is combined with aramid nanofibers, the composite structure formed can effectively disperse stress and prevent premature fracture caused by stress concentration. In addition, the modified aramid fiber exhibits higher fracture strength and modulus during stretching. At the same time, the surface of aramid fiber originally lacks chemically active groups, resulting in low interfacial bonding strength with the matrix material. CNT modification can improve the overall performance of the composite material by increasing the active sites on the fiber surface and improving its wettability and interfacial bonding strength with the matrix material. The high aspect ratio and excellent mechanical properties of CNT enable it to be evenly dispersed in the composite fiber and effectively dissipate energy when subjected to external force. This modification method significantly improves the impact resistance and wear resistance of aramid fiber, making it more durable in high stress and high wear environments.
[0040] In a specific implementation, the aramid fiber filament is prepared by the following modification method:
[0041] (1) Cleaning:
[0042] The aramid fiber filaments were immersed in an acetone solution and subjected to ultrasonic treatment for 30 minutes; then rinsed with deionized water for 3-5 times, placed in a vacuum oven, vacuum dried at 60°C for 4 hours, taken out, and sealed for storage;
[0043] (2) Preparation of modified solution:
[0044] A Tris buffer reagent is prepared by using a dilute hydrochloric acid solution and tris(hydroxymethyl)aminomethane particles, and the Tris buffer is slowly added to a dopamine-HCL solution with a concentration of 2 g / L for multiple times, and the pH is adjusted to 8.5 to obtain a dopamine solution; then, 0.13% by mass of hydroxy carbon nanotube powder CNT is dissolved in anhydrous ethanol solution, and the mass ratio of the hydroxy carbon nanotube powder CNT to ethanol is 5:95, and after ultrasonic dispersion for 1-2 hours, the mixture is added to the dopamine solution, and the mixture is fully stirred and mixed to obtain a modified solution;
[0045] (3) Modification treatment:
[0046] The washed aramid fiber filaments are completely immersed in the modification solution, immersed at room temperature for 24 hours, and then rinsed with deionized water for 3-5 times; finally, dried in a vacuum oven at 60°C for 2 hours to obtain CNT-modified aramid fiber filaments.
[0047] 1. Experiment of aramid fiber filament
[0048] (1) Fiber surface morphology analysis: A Phenom desktop scanning electron microscope (SEM) was used to characterize the microscopic surface changes of a single aramid fiber before and after modification.
[0049] The dopamine solution is added with 0.13% CNT to modify the aramid fiber filaments. The carbon nanotubes doped in the dopamine coating on the fiber surface make the polydopamine coating densely cover the fiber, and the granular protrusions are reduced. Due to the addition of nanofillers, the oxidation self-polymerization of dopamine on the fiber surface is assisted and guided, so that the original polydopamine polymerization points are dispersed, and the coating is more uniform and dense.
[0050] (2) Yarn strength test: The yarn strength test refers to GB / T19975-2005 Test method for tensile properties of high-strength filament yarns, and the strength test is carried out on the aramid yarn before and after modification.
[0051] The tensile load of the modified aramid fiber is significantly higher than that of the unmodified aramid fiber. This is because the aramid fiber has a skin-core structure, and the main load-bearing part is the core layer. The dopamine coating is attached to the fiber surface, which does not affect the original mechanical structure of the aramid fiber, and forms a protective layer on the fiber surface, which disperses part of the load when tensile force is applied, thereby improving the fiber's load-bearing capacity. After CNT doping, the density of the coating is increased, and the coating area applied on the fiber surface is increased, so the tensile load that can be carried is significantly increased, and the overall strength of the aramid filament is increased. The maximum tensile load is increased by 38.57%.
[0052] (4) Fiber surface hydrophilicity test
[0053] The contact angle test was carried out using the insertion method. The fiber was suspended vertically and slowly inserted into a horizontal liquid surface to obtain the fiber surface contact angle and calculate the fiber surface free energy.
[0054] The surface contact angle of the unmodified aramid fiber is 95°, which is hydrophobic, the fiber surface is smooth and flat, and the surface free energy is low. After adding CNT, the contact angle of the fiber is significantly reduced and the surface free energy is increased, which proves that after doping with CNT, it is more conducive to the adhesion of the PDA coating on the fiber surface, the coating is more uniform and dense, the density of active groups is increased, and the wetting performance is significantly enhanced.
[0055] (5) Fiber extraction force test
[0056] Epoxy resin (GCC-135) and curing agent (GCC137) were mixed at a mass fraction of 100:30. The aramid fiber was inserted into a cylindrical tubular mold with a length of 1 mm, and the mixed resin was injected into the mold and cured for 24 hours to complete the single-filament extraction test sample of the aramid fiber.
[0057] Compared with the unmodified aramid fiber, the interface shear strength of the modified aramid fiber increased by 2.95%. The interfacial bonding performance between the fiber and the resin was significantly improved. This is because after the carbon nanotubes were introduced into dopamine, they acted as nanofillers to guide the dopamine to polymerize into a denser coating on the surface of the aramid fiber. The fiber surface was evenly coated, the active groups increased, and the connection sites between the fiber and the resin increased, forming a strong connection.
[0058] On the other hand, the same-direction twisting method has higher breaking strength and breaking elongation in terms of mechanical properties. The product performance of the composite fiber is shown in the following table.
[0059]
[0060] Based on the above composite fiber, the present invention also provides a wear-resistant fabric, which is woven from the composite fiber. The wear-resistant fabric has the properties of the above composite fiber. Due to the high strength and wear resistance of the composite fiber, the fabric is not easy to wear in a high friction environment, and the service life is significantly extended. The synergistic effect of the polyethylene fiber and the CNT modified layer enables the fabric to be used repeatedly for a long time, extending the service life.
[0061] In a preferred embodiment, the wear-resistant fabric adopts a warp knitted structure. Figure 1 As shown in the figure, the warp knitted structure can increase the contact points between fibers through high-density coil arrangement, thereby improving the wear resistance of the fabric. Warp knitted fabrics have good elasticity and can adapt to complex movements and deformations while maintaining high wear resistance. On the other hand, the surface of the warp knitted structure is more uniform, which can better disperse friction and reduce local wear. Through the combination of specific organizational structures and yarns, the wear resistance of the fabric is synergistically improved.
[0062] In a preferred embodiment, the wear-resistant fabric is treated with a wear-resistant coating, and the thickness of the wear-resistant fabric is 0.1 to 0.14 mm. Coating a layer of wear-resistant resin on the surface of the fabric is the simplest and most effective method for improving wear resistance. Adding wear-resistant fillers to the resin and coating it on the surface of the fabric protects the fabric during friction, thereby significantly improving the wear resistance of the fabric.
[0063] Specifically, the wear-resistant coating treatment includes the following steps:
[0064] 100g of titanium boride particles and 12.5g of ethanol thickener were added to 5000g of silicone resin solution, and stirred at room temperature with a magnetic stirrer at a stirring speed of 2000rpm for 30min. After stopping stirring, the solution was coated on the wear-resistant fabric and dried at 80℃ for 6h.
[0065] In this technology, titanium boride particles have excellent performance, high hardness and excellent wear resistance. Silicone resin is a polymer material that combines good film-forming properties, hydrophobic properties, gloss properties, weather resistance, scratch resistance and corrosion resistance. Titanium boride particles are well dispersed in silicone resin, and a coating with excellent performance can be obtained.
[0066] Product experiment: wear-resistant fabric, wear-resistant fabric treated with pure silicone resin coating, and wear-resistant fabric treated with wear-resistant coating were tested respectively. The experimental method and results are as follows.
[0067] 1. The wear resistance of the fabric surface is mainly measured by measuring the wear of the fabric surface. First, cut the coated fabric into a circle with a radius of 12 cm, leaving a small hole in the middle, clean it, and the mass after drying is m0. After coating and drying, the mass is m1. The wear resistance test is carried out. The mass after 100, 300, 500, 1000, 1500 and 2000 times of wear is m2. The wear amount is calculated as:
[0068]
[0069] The calculation formula for the coating amount is: m=m1-m0. The friction times when the first yarn breaks are recorded as the wear times.
[0070] The two coated fabrics have the best wear resistance, which is because the organic silicon resin itself is a resin with excellent wear resistance. The coating contains resin, so the lower the wear rate, the better the wear resistance. The wear resistance of the fabric coated with the organic silicon resin with titanium boride particles is better than that of the pure organic silicon resin coating. This is because titanium boride itself has excellent wear resistance. When it is added to the organic silicon resin system, it can be used as an auxiliary reinforcement, which greatly improves the wear resistance of the entire system. When an appropriate amount of titanium boride particles is added, the wear rate of the coated fabric is higher than that of the pure organic silicon resin coated fabric. This is because the presence of titanium boride particles destroys the good film-forming properties of the organic silicon resin. When the grinding wheel is strongly rubbed, due to poor film formation, the wear probability of the film increases, and the wear rate increases accordingly. Under the same number of frictions, the wear resistance of the wear-resistant fabric is lower than that of the wear-resistant fabric treated with pure organic silicon resin coating and the wear-resistant fabric treated with wear-resistant coating.
[0071] 2. According to national standards, cut the fabric samples into the specified size and use the HD026N electronic fabric strength tester to test the breaking strength of the fabric. Before testing, calibrate the instrument and test the warp strength of the fabric.
[0072] The experimental results show that the tensile breaking strength of wear-resistant fabrics treated with pure silicone resin coating and wear-resistant fabrics treated with wear-resistant coating are far superior to that of ordinary wear-resistant fabrics.
[0073] Due to the presence of resin, the coating viscosity increases, the coating thickness increases, the thickness of the coated fabric increases, and the tensile breaking strength increases. The tensile breaking strength of the coated fabric with titanium boride is less than that of pure silicone resin, and the tensile breaking strength of the coated fabric with titanium boride is not much different from that of pure silicone resin.
[0074] At the same time, as the content of silicone resin increases, the tensile strength at break increases. This is because the presence of the resin increases the viscosity of the coating, the thickness of the coating increases, the thickness of the coated fabric increases, and the tensile strength at break increases.
[0075] like Figure 2 As shown, the present invention also provides a seat cushion, the seat cushion includes a fabric and a filler arranged in the fabric; the fabric is made of wear-resistant fabric treated with a wear-resistant coating. Specifically, the fabric includes an upper surface and a lower surface, the edges of the upper surface and the lower surface are sewn, and an inner cavity for accommodating the filler is formed between the upper surface and the lower surface. Specifically, the filler includes a silicone layer, a first memory foam layer, and a second memory foam layer arranged in sequence from top to bottom.
[0076] Specifically, the silicone layer has a plurality of protrusions, and the protrusions are distributed on the silicone layer at intervals.
[0077] The silicone layer has several protrusions, which are spaced apart from each other. This structure enables the silicone layer to provide good support and pressure dispersion. The silicone itself has high elasticity and stability, and can effectively buffer external pressure.
[0078] The double-layer memory foam design can provide more lasting support and reduce the risk of filling collapse. It can further disperse pressure and improve overall comfort.
[0079] The role of the overall filler structure, the advantages of the multi-layer structure: the combination of the silicone layer and the two layers of memory foam allows the seat cushion to provide good support while effectively dispersing pressure. This structure can meet the needs of different users, whether it is a short break or a long period of office or driving.
[0080] Durability and stability: The combination of memory foam and silicone not only improves comfort, but also enhances the durability of the cushion, allowing it to maintain good performance over long-term use.
[0081] For other structures of the composite fiber, wear-resistant fabric, and cushion described in this embodiment, refer to the prior art.
[0082] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Therefore, any modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention shall still fall within the scope of the technical solution of the present invention.
Claims
1. A composite fiber, characterized in that: The composite fiber adopts a twisted yarn structure, and the composite fiber is a strand of PBO fiber and three strands of polyethylene fiber filaments twisted in the same direction on aramid fiber filaments.
2. A composite fiber according to claim 1, characterized in that: The product specification of the polyethylene fiber filament is 22.22tex / 198f.
3. A composite fiber according to claim 1, characterized in that: The product specification of the aramid fiber filament is 131.11tex / 667f.
4. A composite fiber according to claim 3, characterized in that: The aramid fiber filaments are CNT-modified aramid fiber filaments.
5. A composite fiber according to claim 4, characterized in that: The aramid fiber filament is prepared by the following modification method: (1) Cleaning: The aramid fiber filaments were immersed in an acetone solution and subjected to ultrasonic treatment for 30 minutes; then rinsed with deionized water for 3-5 times, placed in a vacuum oven, vacuum dried at 60°C for 4 hours, taken out, and sealed for storage; (2) Preparation of modified solution: A Tris buffer reagent is prepared by using a dilute hydrochloric acid solution and tris(hydroxymethyl)aminomethane particles, and the Tris buffer is slowly added to a dopamine-HCL solution with a concentration of 2 g / L for multiple times, and the pH is adjusted to 8.5 to obtain a dopamine solution; then, 0.13% by mass of hydroxy carbon nanotube powder CNT is dissolved in anhydrous ethanol solution, and the mass ratio of the hydroxy carbon nanotube powder CNT to ethanol is 5:95, and after ultrasonic dispersion for 1-2 hours, the mixture is added to the dopamine solution, and the mixture is fully stirred and mixed to obtain a modified solution; (3) Modification treatment: The washed aramid fiber filaments are completely immersed in the modification solution, immersed at room temperature for 24 hours, and then rinsed with deionized water for 3-5 times; finally, dried in a vacuum oven at 60°C for 2 hours to obtain CNT-modified aramid fiber filaments.
6. A wear-resistant fabric, characterized in that: The wear-resistant fabric is woven from the composite fiber described in claim 5.
7. The wear-resistant fabric according to claim 6, characterized in that: The wear-resistant fabric adopts a warp knitted structure.
8. The wear-resistant fabric according to claim 7, characterized in that: The wear-resistant fabric is treated with a wear-resistant coating.
9. A seat cushion, characterized in that: The seat cushion comprises a fabric and a filler arranged inside the fabric; the fabric is made of the wear-resistant fabric described in claim 8.
Citation Information
Patent Citations
Preparation method of soft and durable anti-penetrating material
CN107815870A
Cool fiber warp-knitted car seat cushion and preparation method thereof
CN109518353A
Novel anti-cutting fabric
CN111254574A
Method for enhancing interfacial adhesion property of aramid fiber and epoxy resin
CN111979766A